Ethical Issues in Neonatal and Pediatric Clinical Trials - Laventhal, Naomi (2012)
Children have been identified as uniquely vulnerable clinical research subjects since the early 1970s. In this paper we review the historical underpinnings of this designation, the current regulatory framework for pediatric and neonatal research, and common problems in pediatric research oversight. We also present three areas of pediatric and neonatal research (genomic screening, healthy children donating stem cells, and therapeutic hypothermia for neonates with hypoxic-ischemic encephalopathy) that highlight contemporary challenges in pediatric research ethics, including balancing risk and benefit, informed consent and assent, and clinical equipoise.